Reconstructing Permafrost Sedimentological Characteristics and Post-depositional Processes of the Yedoma Stratotype Duvanny Yar, Siberia - Shmelev, Denis; Cherbunina, Maria; Rogov, Victor; Opfergelt, Sophie; Monhonval, Arthur; Strauss, Jens (Frontiers in Earth Science, 2021)
Cryogenic weathering is a key driver of periglacial sediment composition and properties. Selective mineral-grain weathering caused by freeze-thaw cycles in permafrost environments has the ability to dominate this process, leading to silt-rich grain-size distributions. The cryogenic weathering index (CWI) is a promising tool to quantify cryogenic weathering and freezing conditions. It considers the low resistance of quartz to freeze-thaw cycles compared to feldspars. Using this approach, this study aims to decipher post-depositional weathering by reconstructing cryogenic late Pleistocene Yedoma origins of the Yedoma stratotype exposure Duvanny Yar. To estimate the recent environmental endmember and to determine the initial mineral composition of sediment until freezing, the distribution of CWI in the active layer was studied. In addition to CWI, we studied mineral composition, heavy mineral distribution, grain size distribution and grain morphology. We suggest that cryogenic weathering likely altered polygenetic deposits (fluvial, nival, colluvial, lacustrine, alluvial, and aeolian processes) during sediment and ground ice accumulation. Moreover, we found two CWI distribution peaks in the late Pleistocene - Holocene sediments at the boundaries between glacial and interglacial ages. In conclusion, we see that the Duvanny Yar sediment facies varied by CWI, but also with grain-size distribution, suggesting environmental changes during formation. Nevertheless, post-depositional processes like cryogenic weathering have influenced sediment characteristics and should be considered in paleoenvironmental reconstructions.